Code-Mixing Practice on Instagram as an Informal English Learning in Social Media - Nidya Kayla Adhana; Akhmad Haqiqi Ma'mun (Universitas Pahlawan Tuanku Tambusai, 2026)
Code-mixing has become a common linguistic phenomenon in social media communication, particularly among English language learners. Previous studies have examined code-mixing across various digital platforms; however, limited attention has been given to its role in informal English learning through Instagram. Instagram was selected as the research context because it is one of the most popular social media platforms among university students, enabling frequent bilingual interaction through captions and comments in authentic communication. This study aimed to identify the types of code-mixing used in Instagram captions and comments, investigate the reasons for its use, and explore its contribution to informal English learning. A descriptive qualitative approach was employed involving five undergraduate English Education students. Data were collected through documentation of Instagram captions and comments, followed by semi-structured interviews, and were analyzed using thematic analysis. The findings revealed three types of code-mixing: insertion, alternation, and congruent lexicalization, with insertion being the most dominant type. The participants primarily used code-mixing to express feelings, construct identity, and enhance social prestige. Moreover, code-mixing contributed positively to vocabulary acquisition, increased confidence in using English, and encouraged continuous language exposure. These findings suggest that Instagram provides a meaningful environment for informal English learning while facilitating authentic bilingual communication.